2013
DOI: 10.1038/ki.2012.300
|View full text |Cite
|
Sign up to set email alerts
|

High phosphate directly affects endothelial function by downregulating annexin II

Abstract: Hyperphosphatemia is associated with increased cardiovascular risk in patients with renal disease and in healthy individuals. Here we tested whether high phosphate has a role in the pathophysiology of cardiovascular events by interfering with endothelial function, thereby impairing microvascular function and angiogenesis. Protein expression analysis found downregulation of annexin II in human coronary artery endothelial cells, an effect associated with exacerbated shedding of annexin II-positive microparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 43 publications
1
79
1
9
Order By: Relevance
“…NO synthesis, annexin II regulation, etc.) (Lau et al 2011, Di Marco et al 2013. In acromegaly, it may be that potentially beneficial effects of GH and Klotho on endothelial function and NO synthesis are outweighed by IR and hyperphosphataemia, so that there is a net increase in cardiovascular risk.…”
Section: Gh and Klothomentioning
confidence: 99%
“…NO synthesis, annexin II regulation, etc.) (Lau et al 2011, Di Marco et al 2013. In acromegaly, it may be that potentially beneficial effects of GH and Klotho on endothelial function and NO synthesis are outweighed by IR and hyperphosphataemia, so that there is a net increase in cardiovascular risk.…”
Section: Gh and Klothomentioning
confidence: 99%
“…Some recent findings suggest that EMPs are not only markers of endothelial damage but may also be involved in ED, probably because of their protein content. 48 In an elegant study, Di Marco et al 49 recently demonstrated that high phosphate levels induces EMP shedding. After observing the large number of annexin-II positive EMPs, the researchers speculated that the induced EMP shedding decreases intracellular levels of annexin-II and thus results in impaired ECs with thrombotic, inflammatory and anti-angiogenic properties.…”
Section: Indirect Effects Of Phosphate On CV Calcification and Edmentioning
confidence: 99%
“…7 MPs are, therefore, associated with a prothrombotic state and may contribute to acute occlusive events in CKD. It has recently been reported that Pi can increase the generation of MPs from cultured ECs, 12 but the molecular basis of Pi's action is obscure. In this study, we test the hypothesis that hyperphosphatemia elevates intracellular Pi concentration in ECs, resulting in direct global inhibition by Pi ions of phosphoprotein phosphatases.…”
mentioning
confidence: 99%